The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1088/1361-6595/ac9c2c
|View full text |Cite
|
Sign up to set email alerts
|

Guiding effect of runaway electrons in atmospheric pressure nanosecond pulsed discharge: mode transition from diffuse discharge to streamer

Abstract: In this study, the role of runaway electrons (RAEs) during the pulsed breakdown in the atmosphere is investigated. Nanosecond pulsed discharge (NPD) is driven by high-voltage pulses between blade-to-plate electrodes (with the blade as the cathode). RAEs with an energy higher than 10 keV are selected by a titanium foil with a thickness of 1 μm and detected by a beam collector with a front of about 50 ps. The temporal-spatial evolution of the electric field over the NPD period is measured using electric field in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…The analogous observation was made in [63]. The guiding effect of fast electrons was also demonstrated in [82]. The authors showed that the initially diffuse discharge branched and transformed into streamers due to the fast or REs.…”
Section: Streamers At High Overvoltagesmentioning
confidence: 54%
“…The analogous observation was made in [63]. The guiding effect of fast electrons was also demonstrated in [82]. The authors showed that the initially diffuse discharge branched and transformed into streamers due to the fast or REs.…”
Section: Streamers At High Overvoltagesmentioning
confidence: 54%
“…In the course of the research, much attention is paid to the study of nanosecond diffuse discharges in atmospheric air, formed in an inhomogeneous electric field. [1][2][3][4][5][6]. The formation of such discharges is accompanied by the generation of run-away electrons and X-rays.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of such discharges is accompanied by the generation of run-away electrons and X-rays. [1,3,6], and the discharges themselves find practical applications in various scientific and technical fields. Thus, the diffuse discharge formed in the gap with a cathode, which had a small radius of curvature, was used to clean surfaces from carbon, improve adhesion, oxidize and harden the surface of various metals [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…直流电源驱动的一般放电相比,纳秒脉冲放电具有一些特殊的放电特性,如高击 穿电压、高能电子和重叠等离子体通道等 [8][9][10] 。当脉冲宽度短至几纳秒时,气隙 击穿通常发生在亚纳秒或纳秒的时间尺度上,传统的汤森或流注理论不能用于解 释其中的放电现象 [11] 。因此,国内外学者提出了电子崩链模型、快速电离波模型 等多种物理模型来描述纳秒脉冲放电,这些物理模型都认为逃逸电子在纳秒脉冲 放电中起着重要作用,因为它们可以引导电子崩的发展并预电离背景气体 [12,13] 。 为了验证逃逸电子的存在以及研究逃逸电子在纳秒脉冲放电中的作用,研究 人员已经在许多场景中进行了大量研究 [14][15][16][17][18][19] 。早在 1966 年,Frankel 等 [14] 首次在 大气压氦气纳秒脉冲针-板放电产生的 X 射线中间接识别出逃逸电子。随后,研 究人员致力于通过测量纳秒脉冲放电中的 X 射线来研究逃逸电子的物理特性及 机理 [15][16][17] 。由于高速示波器和超快脉冲发生器的发展,自 2003 年以来,许多学 者在实验中直接捕获和测量到逃逸电子 [18] ,这些实验研究为揭示纳秒脉冲放电中 逃逸电子的潜在机制做出了巨大贡献。例如,Beloplotov 等 [19] 在间隙长为 8.5mm 的针-板电极中分别注入了空气和氦气并进行了纳秒脉冲放电实验, 通过对比分析 逃逸电子束流和动态位移电流,发现逃逸电子不仅在间隙击穿期间产生,而且在 间隙击穿之后也会产生。 虽然实验研究取得了诸多进展,但目前仍无法在实验中直接观察和测量逃逸 电子的产生和运动等微观物理过程 [11] 。因此,基于粒子(Particle-in-cell/Monte Carlo collisions,简记为 PIC/MCC)模型 [20] 或流体模型 [21] 的数值模拟,可以作为 研究纳秒脉冲放电物理机理的有力补充手段。例如,Levko 等 [20] 使用 PIC/MCC 模型分析了 0.5-4MPa 压力范围内氮气的纳秒脉冲击穿机理。结果表明,逃逸电 子的产生显著改变了放电的时间和空间动力学。 尽管上述实验和数值模拟研究已经广泛探索了极不均匀电场(例如针-板电极) 中的纳秒脉冲放电中逃逸电子的相关物理机制, 但仍有许多问题尚不清晰。 例如, 通常认为在板-板电极中施加的均匀电场难以达到产生逃逸电子所需的电场阈值, 因此对板-板电极中逃逸电子的产生机制研究较少。然而,Kozyrev 等 [22] 对高压氮 气纳秒脉冲放电进行了数值模拟,他们发现在空间电荷动力学行为的影响下,在 具有初始均匀电场的气隙中会形成局部增强电场区域。此外,纳秒脉冲放电中可 能存在大体积弥散放电 [23] 波形如图1(b)所示,此电压波形用于拟合文献 [24] 的实验研究中使用的纳秒脉冲电 压波形,这种处理手段已在之前的研究中被广泛采用 [25] 。 图1 (a)几何模型示意图,dg代表空气间隙长度;(b)纳秒脉冲电压波形 本文采用Langdon等 [26] 根据文献 [27] 可知,空气中含有大量具有高电子附着系数的氧气,所以空气间 隙中存在自由电子的概率小于0.01%。因此,本研究中假设初始电子的来源是阴 极表面微突起上的场发射,这一过程可以用Fowler-Nordheim方程 [28] 来描述: 1/2 2 7 3/2 6 ( / ) ( ) 6.85 10 6.2 10 exp( )…”
unclassified